2020
DOI: 10.3390/ijms21186575
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecules and Peptides Targeting Glial Cell Line-Derived Neurotrophic Factor Receptors for the Treatment of Neurodegeneration

Abstract: Glial cell line-derived neurotrophic factor (GDNF) family ligands (GFLs) are able to promote the survival of multiple neuronal populations in the body and, therefore, hold considerable promise for disease-modifying treatments of diseases and conditions caused by neurodegeneration. Available data reveal the potential of GFLs for the therapy of Parkinson’s disease, neuropathic pain and diseases caused by retinal degeneration but, also, amyotrophic lateral sclerosis and, possibly, Alzheimer’s disease. Despite pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 109 publications
(200 reference statements)
0
8
0
Order By: Relevance
“…Degeneration of dopamine neurons starts from their synapses and the axons in caudate putamen ( Figure 1 ), whereas cell bodies in the SNpc degenerate later. NTFs are not able to reverse the apoptosis of completely degenerated neurons; instead, they restore the axons of the stressed and degenerating dopamine neurons and their contacts ( Sidorova and Saarma, 2020 ). Thus, the degenerating axons in caudate putamen are the main targets of NTFs, and according to current understanding, the NTFs should be delivered to the axons of the neurons into caudate putamen (discussed in more details below).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Degeneration of dopamine neurons starts from their synapses and the axons in caudate putamen ( Figure 1 ), whereas cell bodies in the SNpc degenerate later. NTFs are not able to reverse the apoptosis of completely degenerated neurons; instead, they restore the axons of the stressed and degenerating dopamine neurons and their contacts ( Sidorova and Saarma, 2020 ). Thus, the degenerating axons in caudate putamen are the main targets of NTFs, and according to current understanding, the NTFs should be delivered to the axons of the neurons into caudate putamen (discussed in more details below).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to NGF that was tested in one patient, four growth factors, glial cell line-derived neurotrophic factor (GDNF), neurturin (NRTN), platelet-derived growth factor (PDGF-BB), and CDNF have been tested in clinical trials in PD patients. The results of the clinical studies with GDNF, NRTN, and PDGF-BB were summarized by Sullivan and Toulouse (2011) , recently updated by Huttunen and Saarma (2019) , Barker et al (2020) , and Sidorova and Saarma (2020) and briefly summarized in Table 1 . The clinical benefit of NTFs in these clinical trials was mostly assessed using Unified Parkinson’s Disease Rating Scale (UPDRS) demonstrating the severity of motor symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…It was recorded that GDNF is an important factor for dopaminergic neuronal survival [ 18 ] and that the elevated level of GDNF could induce the function of dopaminergic neurons and might exhibit a neuroprotective role in PD animal models [ 53 ]. The results in the current experiment showed that both PSE and PJ increased the level of GDNF in the striatum of PQ-injected animals.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that glial cell-derived neurotrophic factor (GDNF) exhibits a prominent neurorestoration and neuroprotection in multiple neurodegenerative diseases, including PD. [ 17 ] It was recorded that GDNF is a crucial factor for the survival of the dopaminergic neurons [ 18 ]. It was investigated in different PD clinical trials since the main hallmark for PD pathology is the dopaminergic neuronal loss in the brain [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation